User Localization in Complex Environments by Multimodal Combination of GPS, WiFi, RFID, and Pedometer Technologies. (31st March 2014) - Dao, Trung-Kien; Nguyen, Hung-Long; Pham, Thanh-Thuy; Castelli, Eric; Nguyen, Viet-Tung; Nguyen, Dinh-Van
Abstract : Many user localization technologies and methods have been proposed for either indoor or outdoor environments. However, each technology has its own drawbacks. Recently, many researches and designs have been proposed to build a combination of multiple localization technologies system which can provide higher precision results and solve the limitation in each localization technology alone. In this paper, a conceptual design of a general localization platform using combination of multiple localization technologies is introduced. The combination is realized by dividing spaces into grid points. To demonstrate this platform, a system with GPS, RFID, WiFi, and pedometer technologies is established. Experiment results show that the accuracy and availability are improved in comparison with each technology individually.